2021
DOI: 10.1001/jamacardio.2020.3151
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of PCSK9 Inhibition With Evolocumab in Reducing Cardiovascular Events in Patients With Metabolic Syndrome Receiving Statin Therapy

Abstract: IMPORTANCEThe PCSK9 inhibitor evolocumab reduced low-density lipoprotein cholesterol and cardiovascular events in the FOURIER randomized clinical trial. Patients with metabolic syndrome (MetS) are at increased cardiovascular risk.OBJECTIVE To investigate outcomes with evolocumab in patients with and without MetS. DESIGN, SETTING, AND PARTICIPANTS The FOURIER trial randomized patients worldwide with stable atherosclerotic cardiovascular disease receiving statin to evolocumab vs placebo with follow-up for a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…This includes patients with recent ACS and those ASCVD and additional CV risk enhancers including diabetes mellitus, metabolic syndrome, polyvascular disease (vascular disease in ≥2 arterial beds), symptomatic peripheral artery disease (PAD), history of MI, MI in the past 2 years, previous coronary artery bypass graft (CABG) surgery, LDL ≥2.6 mmol/L, heterozygous FH and Lp (a) ≥60 mg/dl. 92,[107][108][109][110][111][112][113][114][115] Intensification of lipid-lowering therapy with PCSK9 inhibitors is especially recommended in these subsets of very high risk patients (see Table 3), with or without the addition of ezetimibe, which was used in only a minority of patients in these trials. Use of PCSK9 inhibitor therapy in these subsets of patients was shown to result in rapid and large reductions in LDL-C and in significant CVD event reduction.…”
Section: Pico 4: In Secondary Prevention What Is the Most Appropriate Lipid/lipoprotein Threshold For The Intensification Of Therapy?mentioning
confidence: 99%
“…This includes patients with recent ACS and those ASCVD and additional CV risk enhancers including diabetes mellitus, metabolic syndrome, polyvascular disease (vascular disease in ≥2 arterial beds), symptomatic peripheral artery disease (PAD), history of MI, MI in the past 2 years, previous coronary artery bypass graft (CABG) surgery, LDL ≥2.6 mmol/L, heterozygous FH and Lp (a) ≥60 mg/dl. 92,[107][108][109][110][111][112][113][114][115] Intensification of lipid-lowering therapy with PCSK9 inhibitors is especially recommended in these subsets of very high risk patients (see Table 3), with or without the addition of ezetimibe, which was used in only a minority of patients in these trials. Use of PCSK9 inhibitor therapy in these subsets of patients was shown to result in rapid and large reductions in LDL-C and in significant CVD event reduction.…”
Section: Pico 4: In Secondary Prevention What Is the Most Appropriate Lipid/lipoprotein Threshold For The Intensification Of Therapy?mentioning
confidence: 99%
“…For instance, in cohort studies, under hormonal treatment or chemotherapy, patients who presented an overexpression of LDL-R showed a reduced recurrence-free survival [48]. In this case, a novel possibility is the design of strategies that could modulate the expression of LDL-R on tumoral tissues, it is recommendable taking into account the know-how of the novel treatments directed to PCSK-9, based on monoclonal antibodies [57] and RNAi [58] used in cardiovascular-risk patients.…”
Section: Ldl Associated Mechanismsmentioning
confidence: 99%
“…The median duration of follow-up was 26 months and the study showed that the percentage reduction in LDL-C levels with evolocumab (either 140 mg every 2 weeks or 420 mg every month) was 60%, from a median baseline value of 92 mg/dL to 30 mg/dL [ 155 ]. In addition, evolocumab treatment significantly reduced by 15% the risk of the primary end point (major cardiovascular events, MACE) [ 155 ], with benefits also in patients with diabetes [ 157 ], metabolic syndrome [ 158 ] or prior ischemic stroke [ 159 ]. Moreover, from the whole treated group, 0.3% of patients exhibited the production of binding antibodies against evolocumab, but not neutralizing.…”
Section: Current Drugs To Inhibit Pcsk9mentioning
confidence: 99%